Interfractional renal and diaphragmatic position variation during radiotherapy in children and adults: is there a difference?. (3rd August 2017) - van Dijk, Irma W. E. M.; Huijskens, Sophie C.; de Jong, Rianne; Visser, Jorrit; Fajardo, Raquel Dávila; Rasch, Coen R. N.; Alderliesten, Tanja; Bel, Arjan
Abstract: Background: Pediatric safety margins are generally based on data from adult studies; however, adult-based margins might be too large for children. The aim of this study was to quantify and compare interfractional organ position variation in children and adults. Material and methods: For 35 children and 35 adults treated with thoracic/abdominal irradiation, 850 (range 5–30 per patient) retrospectively collected cone beam CT images were registered to the reference CT that was used for radiation treatment planning purposes. Renal position variation was assessed in three orthogonal directions and summarized as 3D vector lengths. Diaphragmatic position variation was assessed in the cranio-caudal (CC) direction only. We calculated means and SDs to estimate group systematic (Σ) and random errors (σ) of organ position variation. Finally, we investigated possible correlations between organ position variation and patients' height. Results: Interfractional organ position variation was different in children and adults. Median 3D right and left kidney vector lengths were significantly smaller in children than in adults (2.8, 2.9 mm vs. 5.6, 5.2 mm, respectively; p < .05). Generally, the pediatric Σ and σ were significantly smaller than in adults ( p < .007). Overall and within both subgroups, organ position variation and patients' height were only negligibly correlated. Conclusions: Interfractional renal and diaphragmatic position variation in children is smaller than in adults indicating that pediatric margins should be defined differently from adult margins. Underlying mechanisms and other components of geometrical uncertainties need further investigation to explain differences and to appropriately define pediatric safety margins.